The scope of food fraud revisited - Gussow, Karen (Crime, law and social change, 2022)
Food fraud is an emerging field of study in academic literature. The aim of this paper is to evaluate whether current understanding of food fraud in literature is in congruence with incidents of food fraud in the Netherlands. The discussion that follows is based on an analysis of 53 empirical cases on food fraud investigations conducted at the Netherlands Food and Consumer Product Safety Authority (NVWA), the nationwide enforcement body tasked with investigating food fraud. The findings elucidate the differences between food fraud and other (food) crime and highlight the discrepancies with academic definitions to date, most notably with respect to incidents of ‘food laundering’ and by emphasizing the existence of intentional facilitators. We thus suggest adjusting the scope of what type of behavior can be considered as food fraud by conceptualizing three forms of food fraud: food laundering, fraudulent food enhancement, and facilitative food fraud. Food laundering encompasses the use of illegal material as food, whereas fraudulent food enhancement describes a situation where legal food is value-enhanced through deceitful cost-cutting measures. Facilitative food fraud captures the role of facilitative actors that operate illegally and intentionally for economic advantage. Based on these concepts, we suggest a modified definition as follows: food fraud is committed by any actor who is intentionally involved in illegal acts for economic advantage, thus causing or facilitating illegal food to be laundered into the supply chain or for food to be fraudulently value-enhanced. Future research should focus on testing these concepts and this definition with empirical studies from different regions and regulatory settings, and introduce additional data sources outside of enforcement, such as employee or victim surveys.